Effect of Hibiscus Sabdariffa Calyx Extract on Haematologic Indices in Sickle Cell Anaemia In-vitro (African Journal of Biomedical Research, 2022)
We hypothesised that the calyx extract of Hibiscus sabdariffa (HS) may have antisickling potential on account of its calcium antagonistic and antioxidants effects. Five ml of blood was collected from sickle cell anaemia (SCA) patients (n=11). 50µL of blood was incubated with 50µL each of 0.l, 1 and 10mg/ml of HS before adding 50µL of 2% sodium metabisulphite (Na2S2O5) (protective assay). Also, 50µL Na2S2O5 was added to 50µL of blood and then incubated with 50µL each of 0.l, 1 and 10mg/ml of HS (reversal assay). In parallel, 50µL of blood each was incubated with 50µL of 5 mg/ml hydroxyurea and 50µL of 0.9% NaCl (control) respectively. The mean cell haemoglobin concentration (MCHC), mean cell volume (MCV) and mean platelet volume (MPV) were determined. In both the protective and reversal assays, a significant (p
Keywords: Antisickling effect, Hibiscus sabdariffa calyx extract, MCHC, MCV, MPV, Gardos channel blocker